(untitled) (The Journal of Psychology and Sociology, 2013)
This article presents the results of applied research of the motivational component of psychology students educational and professional orientation subjective picture, whose study was carried out using the technique of “Causes for Students’ Educational Activities” by A.A. Rean, V.A. Yakunin and “Study of Life Meaning” by V.Y. Kotlyakov. The study showed the presence of changes in the dynamics of the students’ motives in terms of greater awareness and inner focus, the existence of matches and meanings in the subjective assessment of motives for choosing and learning psychology in further professional psychological activities and expert evaluation of teachers, the existence of trends in the coincidence of the semantic representation of the motivational and conceptual spheres of undergraduate students and psychological experts.